2022
DOI: 10.1101/2022.03.23.22272674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nature prescriptions: a scoping review with a nested meta-analysis

Abstract: Background "Nature prescriptions" are gaining popularity as a form of social prescribing and in response to calls for sustainable healthcare. Our review and meta-analysis appraised evidence of effectiveness of nature prescriptions on various health outcomes. In doing so, we sought to determine the factors that are critical for the success of nature prescriptions, based on Social Cognitive Theory. Methods This is a scoping review with a nested meta-analysis for a subset of outcomes. Five databases were search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“… 47 NBIs are increasingly being used within health services in the form of nature prescriptions with evidence to suggest positive effects of nature prescriptions on depression and anxiety. 95 Given the potential benefits of NBIs on mental health outcomes, future research and public health initiatives should endeavour to evaluate the benefits of NBIs in contrast to current treatment options for individuals from socio-economically deprived communities who experience mental health-related difficulties.…”
Section: Discussionmentioning
confidence: 99%
“… 47 NBIs are increasingly being used within health services in the form of nature prescriptions with evidence to suggest positive effects of nature prescriptions on depression and anxiety. 95 Given the potential benefits of NBIs on mental health outcomes, future research and public health initiatives should endeavour to evaluate the benefits of NBIs in contrast to current treatment options for individuals from socio-economically deprived communities who experience mental health-related difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Unstructured nature prescribing was also assessed (eg recommending walks in local parks or national parks), with incentives such as free passes or motivators such as pedometers or exercise diaries. 1 A scoping review with nested meta-analysis of nature prescribing conducted by Nguyen et al 10 included randomised and non-randomised controlled studies of nature prescribing (86 studies in total). Compared with controls, nature prescription programs resulted in greater reductions in systolic blood pressure (mean difference [MD] -4.9 mmHg [95% CI: -9.6, -0.1 mmHg]; I 2 =65%) and diastolic blood pressure (MD -3.6 mmHg [95% CI: -7.4 to 0.1 mmHg]; I 2 =67%) after the intervention, showing that these programs may be an adjunct to pharmacotherapy.…”
Section: Evidence For Nature Prescribingmentioning
confidence: 99%
“…11,12 The review by Nguyen et al showed how nature prescriptions led to greater increases in daily step counts (MD 900 steps [790, 1010]; I 2 =0%). 10 Physical activity in natural environments is also likely to result in less exposure to air pollution and heat.…”
Section: Evidence For Nature Prescribingmentioning
confidence: 99%
See 1 more Smart Citation
“…by regulating air quality [5]), restores depleted cognitive capacities [6,7], alleviates stress [8], reduces loneliness [9][10][11] and encourages regular health behaviours such as physical activity [12,13]. Meta-analyses indicate interventions that enable people to spend more time in nature increase levels of physical activity and lower risks of depression, anxiety, and high blood pressure [14], providing a compelling and urgent case to support harnessing nature in health care [15,16].…”
Section: Introductionmentioning
confidence: 99%